Persepsi Stakeholder terhadap Kurikulum Berbasis Kompetensi Politeknik Pariwisata Makassar (Studi pada Industri Perhotelan Kota Makassar) - Wim Johannes Winowatan (Jurnal Ad'ministrare, 2018)
The focus of this study is to study the effectiveness of the implementation of the Makassar Polytechnic Competency-Based Curriculum in the hospitality industry. Qualitative studies used in case studies were used to reveal stakeholder perceptions about the application of the Competency-Based Curriculum (KBK) used at the Makassar Tourism Polytechnic. Methodologically, data is obtained through 1) Documentation, 2) In-depth interviews (in-depth interviews), and 3) Library Studies. Key informants are stakeholders who have a direct relationship with the hospitality industry. Among them: General Manager Hotel Jolin, Hotel Vape, Sous Chef Four Point Hotel, Vocational Teacher of Tourism and culinary entrepreneurship. Data collection by gathering participation and in-depth interviews. Data are arranged categorically and chronologically, completed and continuously coded. Strategy to verify data by agreeing to Triangulation, Member Checking and Audit Trail.The results of the study show that the competency-based curriculum is relevant to the needs of the industry, because the curriculum is used in synergy with work systems and procedures in the industry. However, to maximize the relevance between industry and professional competency, it is necessary to increase the professions deepening courses, improve by increasing practicum in professional subjects needed in accordance with the development of modern society.